Penguasaan Kakek pada Hak Asuh Anak di Bawah Umur dalam Perspektif Maqashid Syariah - Setiawati, Lilis; Ismail, Habib; Muhklishin, Ahmad; Arsyad, Mufid; Rakhmat (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2023)
Background. The marriage that every human desires is sakinah, mawadah, and warohmah and in marriage the most desired thing is to be blessed with a child. However, in the reality of married life, many of them end in divorce cases which result in disputes regarding child custody. Children under 12 years old must be raised by their biological mother, but this does not rule out the possibility of being raised by their father. Aim. The aim of this research is to determine the control of custody of minor children to grandfathers in Pekalongan, East Lampung and to analyze the control of custody of minor children to grandfathers from a maqashid sharia perspective. Methods. This type of research is qualitative by describing the facts that occurred in Pekalongan, East Lampung. The data sources in this research are primary data sources and secondary data sources as tools for conducting research. Meanwhile, data collection methods use observation, interviews and documentation. Results. The care of underage children by grandfathers which occurred in Pekalongan, East Lampung occurred because the child's mother was unable to care for the child due to economic factors, so the child was given to the father who apparently could not care for the child well, because his job was as a driver. In this way the child is raised by the grandfather. Mastery of custody of minor children to grandfathers occurs according to the maqashid sharia view, namely hifzun-nafs or caring for the soul and hifdz al-nasl or caring for offspring are said to be able to care for children, such as having affection for children, being physically healthy and having an economy that is able to provide for children's needs.